2010
DOI: 10.1111/j.1467-9248.2009.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Non-Institutionalised forms of Political Participation: A Multi-Level Analysis of 25 Countries

Abstract: Various studies suggest that while institutionalised and electoral forms of political participation are in decline in Western societies, non‐institutionalised forms of participation (like demonstrating, political consumerism or signing petitions) are on the rise. However, this expansion of the political action repertoire of citizens also entails the question of equal participation opportunities. It can be argued that contemporary ideals of democratic participation assume an equal representation of citizens' in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
287
1
26

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 374 publications
(332 citation statements)
references
References 40 publications
18
287
1
26
Order By: Relevance
“…Institutionalized participation relates to contacting a politician or working in a political party or political organization. These forms of participation have in common that most often their format is being governed by institutional rules (Marien, Hooghe & Quintelier, 2010). Noninstitutionalized participation refers to signing petitions, protesting and boycotting products.…”
Section: Methodsmentioning
confidence: 99%
“…Institutionalized participation relates to contacting a politician or working in a political party or political organization. These forms of participation have in common that most often their format is being governed by institutional rules (Marien, Hooghe & Quintelier, 2010). Noninstitutionalized participation refers to signing petitions, protesting and boycotting products.…”
Section: Methodsmentioning
confidence: 99%
“…Marien et al 2010;Verba and Nie 1972;Verba et al 1995). Among the structural factors for unequal participation, income is often found to be a good predictor of whether or not someone participates politically, with others typically being education, gender, and age (Marien et al 2010;Verba et al 1995). These inequalities are thus particularly pronounced when turnout is low, and may translate into differential responsiveness.…”
Section: Understanding Differential Responsivenessmentioning
confidence: 99%
“…Further, with many studies focusing on the determinants of political participation, it has become apparent that there are certain structural inequalities in who participates (e.g. Marien et al 2010;Verba and Nie 1972;Verba et al 1995). Among the structural factors for unequal participation, income is often found to be a good predictor of whether or not someone participates politically, with others typically being education, gender, and age (Marien et al 2010;Verba et al 1995).…”
Section: Understanding Differential Responsivenessmentioning
confidence: 99%
“…Younger people also clearly have a preference for non-institutionalized forms of participation. Based on data from the ISSP survey, Marien, Hooghe and Quintelier (2010) found that non-institutionalized forms of participation increase inequality in terms of education, but strongly reduce or even reverse gender and age inequalities. As such, both institutionalized and noninstitutionalized forms of participation have specific (dis)advantages from the perspective of preserving equal access to democratic decision-making procedures.…”
Section: Literature Review 21 Changing Forms Of Political Participamentioning
confidence: 99%